Advances in magnetic induction hyperthermia - Zhang, Yun-Fei; Lu, Mai (Frontiers in Bioengineering and Biotechnology, 2024)
Magnetic induction hyperthermia (MIH), is a technique that has developed rapidly in recent years in the field of tumor thermotherapy. It implants a magnetic heating medium (millimeter-sized heat seeds, micron-sized magnetic particles and nanometer-sized magnetic fluids, etc.) inside the tumor. The material heats up under the induction of an external alternating magnetic field (100~500 kHz), which causes a high temperature zone to rapidly form in the local biological tissues and induces apoptosis in tumor cells. Magnetic induction hyperthermia has the advantages of high safety, strong targeting, repeatable treatment, and the size of the incision during treatment is negligible compared to surgical resection, and is currently used in clinical treatment. However, the millimeter-scale heat seed heating that is typically used in treatments can result in uneven temperatures within the tissue. Common MIH heating devices are bulky and complex in design, and are not easy for medical staff to get their hands on, which are issues that limit the diffusion of MIH. In this view, this paper will discuss the basic theoretical research on MIH and the progress of MIH-related technologies, with a focus on the latest research and development results and research hotspots of nanoscale ferromagnetic media and magnetic heat therapy devices, as well as the validation results and therapeutic efficacy of the new MIH technology on animal experiments and clinical trials. In this paper, it is found that induction heating using magnetic nanoparticles improves the uniformity of the temperature field, and the magneto-thermal properties of nanoscale ferromagnetic materials are significantly improved. The heating device was miniaturized to simplify the operation steps, while the focusing of the magnetic field was locally enhanced. However, there are fewer studies on the biotoxicity aspects of nanomedicines, and the localized alternating magnetic field uniformity used for heating and the safety of the alternating magnetic field after irradiation of the human body have not been sufficiently discussed. Ultimately, the purpose of this paper is to advance research related to magnetic induction thermotherapy that can be applied in clinical treatment.